1989
DOI: 10.2355/isijinternational.29.92
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of desulfurization in ladle steel refining with powder injection at reduced pressures.

Abstract: +r/(1-Tg/Tl)} """"""""""""""""'(1) of (Fe0+MnO) in the slag, which exerts a large effect on desulfurization as described later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…At the slag/metal interface, the reverse of reaction (1) takes place (effectively transferring sulphur from the slag back to the metal). On the other hand, part of the sulphur (15-25%) is directly oxidised via reaction (14) and leaves the process 3,10 .…”
Section: Sulphur Removal In the Convertermentioning
confidence: 99%
“…At the slag/metal interface, the reverse of reaction (1) takes place (effectively transferring sulphur from the slag back to the metal). On the other hand, part of the sulphur (15-25%) is directly oxidised via reaction (14) and leaves the process 3,10 .…”
Section: Sulphur Removal In the Convertermentioning
confidence: 99%
“…Some researchers recommended [61][62][63] that the oxygen activity of molten steel at the slag-metal interface a O,interface , rather than that of molten steel bulk a O,bath , is more reasonable to represent the oxygen activity of molten steel at the slag-metal interface and to affect the desulfurization reactions seriously. Considering that the LF refining process proceeds with higher binary basicity of slags as well as lower a O,bath of molten steel, it is more logical that the a O,interface of molten steel at the slagmetal interface, i.e., at desulfurization zone, is determined based on the equilibrium of species in molten steel and their corresponding oxides in slags.…”
Section: Comparison Of Oxygen Activity Of Molten Steel At Slag-metal mentioning
confidence: 99%
“…Tsujino et al pointed out that oxygen activity at slag–steel interface was related to both the (FeO + MnO) content of slag and the dissolved oxygen activity of steel. In the present experiments, the dissolved oxygen activity of steel estimated by Al–O equilibrium thermodynamics was almost the same for all the heats, thus the oxygen activity at slag–steel interface was mainly related to the (FeO + MnO) content of slag, which indicated that (FeO + MnO) content in slag can be also decreased by increasing silicon content in steel.…”
Section: Resultsmentioning
confidence: 99%